Effects of Photosynthetic Activity Radiation (PAR) on Green Mustard Plant Growth (Brassica rapa var. parachinensis L.) - Ratini, Ni Nyoman; Supardi, I Wayan; Nurfadhillah, Yuli (BULETIN FISIKA, 2019)
A research on the effect of photosynthetic active radiation (PAR) on the growth of green mustard plants has been conducted. The radiation source used is sunlight. Samples have been grouped as a sample which treated by red filter (P1), by orange filter (P2), by purple filter (P3), by green filter (P4), by blue filter (P5) and a sample without filter as a control (P0). Each sample consisted of four plants. The planting was carried out using polybags with compost media. Observations were made from the nursery phase to the slow vegetative phase (day 3 rd , when all plants had grown shoots until day 63 rd of the harvest). Parameters measured include light intensity, plant height and number of leaves. Measurement is done every three days. Also it measured plant biomass on the last day of observation (63 rd day). The results showed that the intensity of each sample had an impact on the harvest. The best growth rate is obtained in P2, both in the nursery phase and fast vegetative phase i.e. 0.119 cm/day and 0.194 cm/day, respectively. While the highest growth rate was obtained in the P3 sample, namely the slow vegetative phase (0.035 cm/day). Overall the best planting results were obtained in P2 samples with plant height of 23.18 cm, number of leaves of 12 strands and plant biomass of 33.56 g.